2022
DOI: 10.1111/jfd.13666
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with Pediococcus pentosaceus enhances the innate immune response in and promotes growth of Litopenaeus vannamei shrimp

Abstract: To reach the sustainable development goals on health management in Litopenaeus vannamei shrimp culture, Pediococcus pentosaceus AB01 was supplemented in shrimp diet. In this study, the control diet and three experimental diets containing P. pentosaceus AB01 (108, 109, 1010 CFU/g) were separately introduced to L. vannamei for a 28 days feeding trial. After the feeding trial, percent weight gain, feeding efficiency, and feed conversion ratio (FCR) were significantly elevated in L. vannamei administered with P. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The current study showed that Pediococcus pentosaceus at a dose of 5-10 µL L -1 can increase survival rate, MBW, and biomass and can reduce YVC, GVC, and TVC in the early phase (M 3) and late period of infection (PL 10) by V. harveyi, although it was not statistically significant. Previous research conducted by Le et al (2022) showed that the addition of P. pentosaceus in shrimp feed could enhance the immunity of whiteleg shrimp. Adel et al (2016), Won et al (2020), andThao et al (2021) also reported that a concentration of 10 8 CFU g -1 of P. pentosaceus to shrimp increased survival rate, growth performance, digestive enzyme activity, immunity, histological conditions of the digestive tract, immune gene expression, and their tolerance to V. anguillarum and V. parahaemolyticus infections and was able to reduce TVC.…”
Section: Discussionmentioning
confidence: 98%
“…The current study showed that Pediococcus pentosaceus at a dose of 5-10 µL L -1 can increase survival rate, MBW, and biomass and can reduce YVC, GVC, and TVC in the early phase (M 3) and late period of infection (PL 10) by V. harveyi, although it was not statistically significant. Previous research conducted by Le et al (2022) showed that the addition of P. pentosaceus in shrimp feed could enhance the immunity of whiteleg shrimp. Adel et al (2016), Won et al (2020), andThao et al (2021) also reported that a concentration of 10 8 CFU g -1 of P. pentosaceus to shrimp increased survival rate, growth performance, digestive enzyme activity, immunity, histological conditions of the digestive tract, immune gene expression, and their tolerance to V. anguillarum and V. parahaemolyticus infections and was able to reduce TVC.…”
Section: Discussionmentioning
confidence: 98%
“…The probiotics, mainly those of the lactobacillus and bifidobaterium genera, such as Lactobacillus plantarum [ 53 , 54 ], Lactobacillus rhamnosus GG [ 55 ], Lactobacillus paracasei [ 23 ], Bifdobacterium bifdum [ 56 ], and Bifidobacterium animalis [ 16 ], can combat the influenza virus infection through regulating the immune response. The probiotic of Pediococcus pentosaceus has been shown to have immunomodulatory effects [ 30 , 31 , 32 ]. However, it is not known if it has an anti-influenza effect.…”
Section: Discussionmentioning
confidence: 99%
“…Pediococcus pentosaceus is Gram-positive facultative anaerobic lactic acid bacteria, which has several beneficial properties, such as antimicrobial [ 24 ], detoxifying [ 25 ], lipid-lowering [ 26 ], anticarcinogenic [ 27 ], intestinal disease-alleviating [ 28 , 29 ], and immune-enhancing activities [ 30 , 31 , 32 ]. However, it is unknown whether oral administration with P. pentosaceus is effective against respiratory viral infections.…”
Section: Introductionmentioning
confidence: 99%